Supracondylar fracture of femur: our experience of treatment with locking compression plate from rural Maharashtra - Paknikar, Kiran P.; Malve, Shekhar; Kulkarni, G. S.; Kulkarni, M. G.; Kulkarni, S. G.; Takalkar, Anant A. (International Journal of Research in Orthopaedics, 2019)
Background: Surgical treatment of supracondylar or intercondylar distal femoral fractures (AO/OTA types 33-A to 33-C) remains a significant surgical challenge with significant complication rates. Supracondylar and intercondylar fractures of femur are very often difficult to treat and they are notorious for many complications. We have studied use of LCP (locking compression plate) in the treatment of metaphyseal fractures. These implants improve fracture healing, especially in osteoporotic bone due to better holding capacity. Objective wass to assess the efficacy of LCP in maintenance of post-operative distal femoral alignment and in preventing post-operative varus collapse in supracondylar fracture of femur. Methods: Prospective Longitudinal observational study Conducted at Post Graduate Institute of Swasthiyog Pratishthan, Miraj, Maharashtra involving 50 patients with supracondylar fracture. The fractures were classified as supracondylar femur fracture (AO/OTA type 33) (A- C). Fractures that were supracondylar with significant proximal fracture extension were classified as an AO/OTA type 33 fracture unless there was a separate diaphyseal fracture. Data was analysed by using SPSS 16.0 version and expressed as percentages. Results: Majority of patients were from 30-39 years age group i.e. 32%. Majority of patients were males i.e. 46 (92%). 7 (14%) patients had healing time <4 months. 24 (48%) patients had healing time between 4-6 months. 19 (38%) patients had healing time more than 6 months. To assess the overall results, we used Knee society score. In 38% of patients, we found excellent results. Good and fair results were seen in 32% and 26% of patients. Conclusion: Locking compression plate is an ideal implant for fixation of supracondylar fracture of femur 33 (A-C) especially in C3 type where articular comminution is present.